Blue Water Footrpint- Industrial Water Consumption Nexus: A Case of Water Supply for Industrial Activities in Semambu Water Treatment Plant - Edriyana, Abd Aziz; S. N., Moni; Noraini, Yussof (IOP Publishing, 2021)
Water supply and industrial activities have a common attribute of being insufficient water resources. Both are involved in water footprint and water consumption Nexus, meaning that industrial water consumption is impacting the water footprint of water treatment plants within the same area. Therefore, in order to achieve the environmental sustainability of water resource, the requirement of having effective approach in water utilisation accounting is crucial. Thus, water consumption for industrial activities and water footprint of Semambu water treatment plant has been a case study to link the nexus. As the industrial development is expanding each year, water demand for water supply also increases. Generally, heavy industrial activities consume more water than the other types of industries. In this study, heavy industrial activities of water consumption show an impact towards total water footprint of the particular water treatment plant in Kuantan river basin. In 2018, the percentage of highest industries that exist is manufacturing sector with 32% while the lowest is 1% compared to 2015, 2016 and 2017 that only scored 30% for manufacturing sector respectively. This shown that there is an increment growth in manufacturing sector in 2018 when they suddenly go up 2% higher compared to 3 years previously. The results focus on total water footprint accounting of Semambu water treatment plant (WTP) and the impact of total blue water consumptions for industrial activities. Finally, total water footprint of water treatment plants in Kuantan river basin will be sustained to cater the industrial needs except for Semambu WTP since Semambu is a gazetted area for industrial. Hence the new method of water utilisation for the industrial activities must be proposed to decrease the dependent towards WTP, especially in Semambu area.